Viscoelasticity and Thermodiffusion in Electric Field - Jędrzejczyk-Kubik, J. (Фізико-математичне моделювання та інформаційні технології, 2006)
Basic equations for description and modelling of electric, thermal and diffusion processes in multicomponent viscoelactic structures under presence of the external electric field are presented. The corresponding constitutive relations are analyzed.